2023
DOI: 10.1101/2023.04.20.537757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic basis of aposematic coloration in a mimetic radiation of poison frogs

Abstract: The evolution of mimicry in a single species or population has rippling inter and intraspecific effects across ecological communities, providing a fascinating mechanism of phenotypic diversification. In this study we present the first identification of genes underlying Müllerian mimicry in a vertebrate, the Peruvian mimic poison frog,Ranitomeya imitator. We sequenced 124R. imitatorexomes and discovered loci with both strong divergence between different mimetic morphs and phenotypic associations within an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“… Liu et al 2014 ; Posso-Terranova and Andrés 2017 ; Stuckert et al 2019 ; Rodríguez et al 2020 ; Stuckert et al 2024 ; Twomey, et al 2020a ). In addition, several studies have identified genes related to color development under positive selection in aposematic species ( Rodríguez et al 2020 ; Linderoth et al 2023 ; Rubio et al 2024 ). Historically, evolutionary biologists have predicted that aposematism, driven by predator-imposed selective pressures, causes sympatric phenotypes among closely related species to converge on a single color pattern to promote accelerated predator learning ( Müller 1879 ; Mallet and Joron 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Liu et al 2014 ; Posso-Terranova and Andrés 2017 ; Stuckert et al 2019 ; Rodríguez et al 2020 ; Stuckert et al 2024 ; Twomey, et al 2020a ). In addition, several studies have identified genes related to color development under positive selection in aposematic species ( Rodríguez et al 2020 ; Linderoth et al 2023 ; Rubio et al 2024 ). Historically, evolutionary biologists have predicted that aposematism, driven by predator-imposed selective pressures, causes sympatric phenotypes among closely related species to converge on a single color pattern to promote accelerated predator learning ( Müller 1879 ; Mallet and Joron 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are four known R. imitator color morphs that occur in sympatry with three congeneric model species ( Symula et al 2001 ; Stuckert et al 2014 ). Significant progress has been made in identifying the genes underlying color production in poison frogs ( Stuckert et al 2019 ; Twomey, et al 2020a ; Rodríguez et al 2020 ; Linderoth et al 2023 ). Of particular relevance is a recent study by Stuckert et al (2024) which examined gene expression of whole-skin samples from R. imitator , Ranitomeya fantastica , and Ranitomeya variabilis.…”
Section: Introductionmentioning
confidence: 99%